A sip of Aesop - Yolen, Jane.; Aesop; Barbour, Karen (New York : Blue Sky Press, 1995)
Retells, in verse, thirteen fables from the Greek slave, Aesop.
Why Aesop? -- The hare and the tortoise -- The tortoise and the eagle -- The dog and the bone -- The lion and the mouse -- The fox and the grapes -- The fox and the crow -- The grasshopper and the ants -- The mice in council -- The frog and the ox -- The boy who cried wolf -- The fox and the stork -- The dog in the manger -- Counting your chickens -- About Aesop.
Elem. School Library Collection.
School Library Journal.
Bulletin (Center for Children's books).
4.4
K-3
Keywords: Aesop's fables -- Adaptations -- Juvenile literature; Aesop's fables; Aesop's fables; Fables; Stories in rhyme; Fables; Stories in rhyme; Didactic poetry; Fables; Stories in rhyme